HBR's 10 must reads on strategy. - McLain, Paul (HBR's 10 must reads (Series), 2022)
Is your company spending too much time on strategy development-with too little to show for it? If you read (or listen to) nothing else on strategy, listen to these ten articles (featuring "What Is Strategy?" by Michael E. Porter). We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you catalyze your organization's strategy development and execution. HBR's 10 Must Reads on Strategy will inspire you to: distinguish your company from rivals; clarify what your company will and won't do; craft a vision for an uncertain future; create blue oceans of uncontested market space; use the Balanced Scorecard to measure your strategy; capture your strategy in a memorable phrase; make priorities explicit; allocate resources early; and clarify decision rights for faster decision making. This collection of bestselling articles includes: featured article "What Is Strategy?" by Michael E. Porter, "The Five Competitive Forces That Shape Strategy," "Building Your Company's Vision," "Reinventing Your Business Model," "Blue Ocean Strategy," "The Secrets to Successful Strategy Execution," "Using the Balanced Scorecard as a Strategic Management System," "Transforming Corner-Office Strategy into Frontline Action," "Turning Great Strategy into Great Performance," and "Who Has the D? How Clear Decision Roles Enhance Organizational Performance."